Scanning probe microscopy investigation of the mechanisms limiting electronic transport in substrate‐supported graphene. Issue 7 (19th June 2013) - Giannazzo, F.; Fisichella, G.; Nigro, R. Lo; Fiorenza, P.; Franco, S. Di; Marino, A.; Piluso, N.; Rimini, E.; Roccaforte, F.
Abstract: The scattering mechanisms limiting electronic transport in substrate‐supported graphene have been investigated by mapping the electron mean free path (l) in graphene on substrates with different dielectric permittivities, i.e. SiO2 (κSiO2 =3.9), 4H‐SiC (0001) (κSiC =9.7) and SrTiO3 (001) (κSrTiO3 =330). From the analysis of the local l versus gate bias curves, histograms and nanoscale maps of the densities of charged impurities (NCI ) have been extracted. l was found to increase from (107±6) nm to (218±11) nm moving from SiO2 to SiC substrate, whereas a decrease to (179±5)nm was found for gra‐ phene on SrTiO3 . Furthermore, a clear correlation between the minima in the l maps and the maxima in the NCI maps was obtained for graphene on SiO2 and SiC, whereas the two maps are uncorrelated in graphene on SrTiO3 . These results indicate that charged impurity scattering is the main source of the lateral inhomogeneity of l on lower κ substrates, like SiO2 and SiC, whereas a different scattering mechanism (probably resonant scattering) must be invoked as the origin of the nanoscale variations of l in graphene on high‐κ substrates like SrTiO3 . (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)